Pivot or perish: hazards of selling clothes on Instagram. (March 2022) - Ayres, Jennifer Lynn
In this paper I outline some of the hazards vintage sellers experience, and the pressure they face, while selling online via Instagram. I argue that the conditions of precarity, overwork, and burnout common to these informal and self-made enterprises were magnified by the COVID-19 pandemic.